Optimal measurement placement using PSO for state estimation - Rosli, H.M.; Mokhlis, Hazlie; Bakar, A.H.A. (2012)
This paper presents an effective method based on Particle Swarm Optimization (PSO) to identify the optimal measurement placement of power system state estimation. The main objective is to simplify the complexity in finding the best measurement placement and provide a high accuracy level of estimated state. The effectiveness of the proposed method is tested using the IEEE 30 bus system. Pseudo measurements of load injection are included as measurement data in assisting the state estimation computation. Â© 2012 IEEE.